Assessment of Aspergillus fumigatus Burden in Pulmonary Tissue of Guinea Pigs by Quantitative PCR, Galactomannan Enzyme Immunoassay, and Quantitative Culture - Vallor, Ana C. (American Society for Microbiology (ASM), 2008)
Early diagnosis of invasive pulmonary aspergillosis is problematic in some patient groups due to the lack of rapid, sensitive, specific, and reliable diagnostic tests. Fungal burden and therapeutic efficacy were assessed by survival, quantitative culture (CFU counts), galactomannan enzyme immunoassay (GM-EIA), and quantitative PCR (qPCR) in a new guinea pig model of invasive pulmonary aspergillosis using an aerosol challenge. At 1 day postinfection, qPCR determined that the pulmonary fungal burden was 2 log(10) higher than that determined by CFU counting and increased significantly (P < 0.03) over time. In contrast, the tissue burden assessed by CFU counting did not rise over the course of the study. Therapy with the antifungal drug voriconazole produced statistically significant decreases in pulmonary fungal burden, as detected by CFU counting (P < 0.02), qPCR, and GM-EIA (both P < 0.0002). Daily assessment of the progression of fungal infection in serum was performed by qPCR and GM-EIA. GM-EIA demonstrated a statistically significant reduction in the fungal load on days 6 and 7 in voriconazole-treated animals compared to time-matched controls (P < 0.02). Confirmation of fungal tissue burden by two or more methods should provide a more precise account of the burden, allowing improved assessment of diagnostic and therapeutic strategies in invasive pulmonary aspergillosis.